B lymphocyte-specific protein binding near an immunoglobulin kappa-chain gene J segment. - Weaver, D (1987)
Nuclear extracts from pre-B and B cell lines contain a nuclear DNA binding protein (kappa locus protein, KLP) that specifically recognizes a DNA sequence in the immunoglobulin kappa light chain joining (J) segment gene region. KLP is not observed in mature B cells, T cells, or nonlymphoid cell types. Two tandem binding sites for KLP designated KI and KII have been identified by methylation interference analysis to be immediately proximal to the J kappa 1 nonamer-heptamer recognition sequences and separated by 38 base pairs from each other. Fragments of DNA containing KI and KII sites compete for binding to KLP, and both protein-DNA complexes have the same electrophoretic mobility. Other flanking sequences of immunoglobulin gene fragments do not bind to KLP. The position of KLP-DNA binding and its tissue-specific expression suggest that it may be involved in the regulation of lymphoid gene DNA rearrangements by targeting recombinase to the kappa-chain gene region.